2014
DOI: 10.1097/brs.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Pulmonary Function in Children With Early-Onset Scoliosis Using Magnetic Growth Rods

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 18 publications
1
43
0
1
Order By: Relevance
“…In a series of 140 patients, with a mean follow-up of 5 years, Bess et al reported that the risk of complications increased by 24% for each additional surgical procedure performed [16]. The MCGR technology was developed to overcome the disadvantages of previous growing rod systems [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a series of 140 patients, with a mean follow-up of 5 years, Bess et al reported that the risk of complications increased by 24% for each additional surgical procedure performed [16]. The MCGR technology was developed to overcome the disadvantages of previous growing rod systems [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Each actuator holds a small cylindrical magnet, which is rotated when stimulated by an external remote controller (ERC) with subsequent MCGR lengthening. As a result MCGRs lengthening is performed noninvasively in the outpatient clinic without the necessity for general anesthesia, invasive surgery, or their associated risks [7][8][9][10][11]. Distraction of MCGRs can also be performed more regularly, which may mimic normal spine growth more accurately than earlier growing rod systems [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCGRs are gaining in popularity among patients and surgeons as they are the least invasive technique for patients with a high degree scoliosis [6][7][8][9][10][11], both for primary operations and conversion cases from the traditional growing rods [12]. Once implanted (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in 15 patients aged 2-10 years managed by VEPTR, they found no correlation between improvement in Cobb angle and evolution of FVC at 13 months' follow-up. Yoon et al, in 6 children with neuromuscular scoliosis aged 5-10 years, reported the effect of spinal distraction by MAGEC Âź magnetic rods on respiratory function [35]; at 2 years' follow-up, Cobb angle showed 34 ‱ improvement, FVC 14% and MEVS 17% over initial values. These results may have been due to early surgery and iterative non-invasive lengthening, limiting fibrous parietal retraction.…”
Section: Effect Of Distractionmentioning
confidence: 99%